2017
DOI: 10.1105/tpc.17.00019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of WRINKLED1 by KIN10 Results in Its Proteasomal Degradation, Providing a Link between Energy Homeostasis and Lipid Biosynthesis

Abstract: (J.S.) WRINKLED1 (WRI1), a member of the APETALA2 (AP2) class of transcription factors, positively regulates glycolysis and lipid biosynthesis in Arabidopsis thaliana. Here, we identify mechanistic links between KIN10, the major SUCROSE NON-FERMENTATION1-RELATED KINASE1 involved in sugar/energy homeostasis, and the posttranslational regulation of WRI1. Transient expression of WRI1 with OLEOSIN1 in Nicotiana benthamiana stimulates triacylglycerol accumulation, but their coexpression with KIN10 abrogates this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 60 publications
6
140
0
1
Order By: Relevance
“…That WRI1 expression did not differ significantly between adg1suc2 and the wild type supports this view. The data presented here, that elevated sugar correlates with increased accumulation of WRI1, is consistent with the previously proposed model of WRI1 stabilization upon Suc-mediated inhibition of KIN10 (Zhai et al, 2017). This also supports our model for a dual role for sugar in providing carbon skeletons for FA synthesis and through inhibiting KIN10 activity and, thereby, stabilizing WRI1.…”
Section: Suc Favors Tag Biosynthesissupporting
confidence: 80%
See 2 more Smart Citations
“…That WRI1 expression did not differ significantly between adg1suc2 and the wild type supports this view. The data presented here, that elevated sugar correlates with increased accumulation of WRI1, is consistent with the previously proposed model of WRI1 stabilization upon Suc-mediated inhibition of KIN10 (Zhai et al, 2017). This also supports our model for a dual role for sugar in providing carbon skeletons for FA synthesis and through inhibiting KIN10 activity and, thereby, stabilizing WRI1.…”
Section: Suc Favors Tag Biosynthesissupporting
confidence: 80%
“…Increased levels of sugar correlated with increased accumulation of total FA and TAG along with increased rates of FA synthesis. This likely results from a combination of two mechanisms: (1) through increasing the supply of carbon skeletons, ATP, and reductant (Sanjaya et al, 2011); and (2) via inhibiting the KIN10-dependent degradation of WRI1 (Zhai et al, 2017). Relative to the wild type, the adg1suc2 double mutant accumulated more than 80-fold higher leaf sugar, 10-fold more TAG, and substantially higher levels of WRI1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WRI1 also is a positive regulator of glycolysis and lipid biosynthesis in Arabidopsis, and recently, phosphorylation of WRI1 by AKIN10 was shown to result in its proteasomal degradation (Zhai et al, 2017). This AKIN10-dependent degradation of WRI1 provides a homeostatic mechanism that favors lipid biosynthesis when intracellular sugar levels are elevated and AKIN10 is inhibited.…”
Section: Anterograde Signals To Organelles Via Phosphorylation Of Tramentioning
confidence: 99%
“…In general, SnRK1-mediated transcriptional reprogramming results in the downregulation of energy-consuming processes and the induction of catabolic pathways to provide alternative energy sources. Although the broad effect on transcription and the specificity that is required to respond to a particular stress are likely to require modulation of a range of different downstream target proteins, only a few transcription factors representing potential direct SnRK1 substrates have been identified (Kleinow et al, 2009;Tsai and Gazzarrini, 2012;Jeong et al, 2015;O'Brien et al, 2015;Zhai et al, 2017). Recently, Mair et al (2015) identified the Arabidopsis transcription factor bZIP63 as a key regulator of the starvation response and a direct target of the SnRK1 kinase.…”
mentioning
confidence: 99%